New synonyms and a new subspecies of Macrogomphus Selys, 1858 (Odonata: Gomphidae) from continental south-east Asia - Kosterin, Oleg E. (Zootaxa, 2019)
The taxa of the genus Macrogomphus Selys, 1858 occurring in continental south-east Asia are reconsidered. Macrogomphus rivularis Förster, 1914 (described from Vietnam), M. borikhanensis Fraser, 1933 (described from Laos), and M. guilinensis Chao, 1983 (described from China), are synonymised with M. albardae Selys, 1878. The relationship and conspecificity of the latter with M. parallelogramma Burmeister, 1839 are doubtful, perhaps they are bona species. Males of M. albardae (and seemingly of parallelogramma as well) are approximately trimorphic for the pale pattern of the abdominal S3–S6, being of either a ‘dashed morph’ (with small isolated anteriolateral spots and conspicuous middorsal streaks), or a ‘ringed morph (with broad anterior rings and less conspicuous middorsal streaks), or an ‘intermediate morph’. Validity of the species M. matsukii Asahina, 1986 is doubted; its holotype could be an aberrant male of M. albardae. The main diagnostic character of M. albardae, M. phalantus Lieftinck, 1935 and probably M. parallelogramma, is clarified to be the structure of the cercus inner branch. M. phalantus jayavarman subsp. nov. is described from temporarily inundated forest at the northern bank of the great Lake Tonlé Sap of Cambodia (Siem Reap Province, 1.5 km SSW of Kampong Pluk village, 13.1956° N, 103.9725° E, 3 m a.s.l.), which is ca 1,300 km north and overseas from the presumed range of M. phalantus phalantus.